THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE ON FIRM VALUE WITH COMPETITIVE ADVANTAGE AS A MEDIATING VARIABLE - Anom Vania Febriani; Luh Gede Krisna Dewi (Adisam Publisher, 2025)
This study is motivated by the increasing attention to ESG disclosure in the energy sector of the Indonesia Stock Exchange (IDX) and the ongoing debate regarding whether such practices enhance firm value through competitive advantage. The purpose of this research is to examine the effect of ESG disclosure on firm value with competitive advantage as a mediating variable. Grounded in signaling theory, ESG disclosure is positioned as a credible signal of managerial quality, accountability, and corporate commitment that reduces information asymmetry, lowers risk, and creates opportunities for cost and differentiation advantages valued by the market. A quantitative approach was applied to 203 observations of energy issuers during 2021–2023 using purposive sampling. Firm value was proxied using Tobin’s Q, competitive advantage was measured through EV/IC, and ESG disclosure was constructed using GRI 400, GRI 300, and GRI 2 indicators. Mediation analysis was performed using the Baron and Kenny regression method in SPSS. The findings show that ESG disclosure has a positive effect on firm value. Environmental disclosure positively affects competitive advantage, whereas social and governance disclosures do not. Competitive advantage positively influences firm value and partially mediates the effect of environmental disclosure on firm value, but does not mediate social or governance disclosure. The results confirm that material and operationally linked ESG disclosure is more effective in enhancing valuation than disclosure conducted merely for formal compliance.